SYNTHESIS, CHARACTERIZATION, AND BIOLOGICAL EVALUATION OF AZETIDINONES BY MODIFYING THE PHARMACOPHORIC SITES USING BETTI’S PROTOCOL OF 8-HYDROXYQUINOLINE PRECURSOR - HIMANI N. CHOPDE (International Journal of Pharma and Bio Sciences, 2014)
An efficient synthesis of series of different novel β-lactams via cycloaddition reaction (Staudinger reaction) of Schiff base has been reported in the present communication. A series of newly substituted 8-hydroxyquinoline Schiff base derivatives have been synthesized efficiently following Betti’s condensation protocol with 8-hydroxyquinoline and different aldehydes under ambient reaction conditions. The structures of the newly synthesized Schiff base derivatives and β-lactams were confirmed by IR, 1H NMR, elemental analysis and mass spectroscopic data. In-vitro anti-bacterial evaluations of β-lactams were done against gram-positive and gram-negative bacterial strains using the well diffusion method. It has been observed that some of these derivatives posses potent anti-bacterial characteristics against these bacteria.